Facile fabrication of water-dispersible nanocomposites based on hexa-peri-hexabenzocoronene and Fe3O4 for dual mode imaging (fluorescent/MR) and drug delivery. Issue 71 (5th December 2018) - Song, Meng-Meng; Xiang, Hui-Hui; Fei, Meng-Yu; Lu, Da-Peng; Jiang, Tong-Cui; Yu, Yong-Qiang; Liu, Rui; Shen, Yu-Xian
Abstract : Water-dispersible, stable and biocompatible dandelion-like Fe3 O4 /HBC@F127 nanocomposites were facilely developed for dual mode imaging (fluorescent/MR) and drug delivery. Abstract : The facile fabrication of multifunctional nanocomposites (Fe3 O4 /HBC@F127) consisting of superparamagnetic Fe3 O4 nanoparticles and fluorescent organic hexa- peri -hexabenzocoronene (HBC) molecules incorporated in block copolymer diacylphospholipid–polyethyleneglycol F127 have been demonstrated for dual mode imaging (fluorescent/MR) and drug delivery. The obtained nanocomposites were water-dispersible, stable and biocompatible, as confirmed by dynamic light scattering (DLS) and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Relativity measurements showed a T 2 relaxivity ( r 2 ) of 214.61 mM −1 s −1, which may be used as T 2 -weighted MR imaging agents. In vitro imaging studies indicated that the nanocomposites had good MR and fluorescence imaging effects with low cytotoxicity. Besides, the developed nanocomposites could also be applied as drug delivery vehicles. Doxorubicin (DOX) loaded Fe3 O4 /HBC@F127 nanocomposites significantly inhibited the growth of human hepatoma cells (HepG2). These findings suggested that the facile synthesized multifunctional nanocomposites may be used as a platform for dual mode imaging (both MR and fluorescence) and drug delivery.